Third-line Salvage Chemotherapy for Recurrent Carcinoma of the Cervix is Associated With Minimal Response Rate and High Toxicity. (August 2018) - Manders, Dustin B.; Kehoe, Siobhan M.; Miller, David S.; Lea, Jayanthi S.; Richardson, Debra L.
Abstract : Background: Metastatic and recurrent cervical cancer is rarely a curable disease. Systemic chemotherapy is typically recommended for treatment based on clinical trials in the first-line or second-line setting. Rare patients who progress through 2 salvage regimens will have the performance status, medical ability, and desire to continue cytotoxic therapy. For these patients, there are no data to provide effective counseling regarding expected response rates (RRs) and toxicities. We sought to review our experience with this patient population. Methods: A single institution review was performed of all patients treated for cervical cancer between January 1, 2000 and June 30, 2013. Eligible patients were those who received at least 3 unique salvage chemotherapy regimens following primary surgery or radiation. RRs, survival statistics and toxicities were evaluated. Results: Twenty-three of 710 (3.2%) patients treated for cervical cancer met eligibility criteria. Nineteen received 2 or more cycles of a third-line regimen and were assessed for response and progression-free survival. The remainder were included in analysis of overall survival and toxicity. The RR to third-line chemotherapy was 10% (1 complete, 1 partial). An additional 27% achieved stable disease. In total, 57% suffered a grade 3 or 4 toxicity. The progression-free survival from the beginning of third-line therapy was 3.8 months, and the overall survival was 7.4 months. Conclusions: Patients eligible to receive third-line chemotherapy for metastatic and recurrent cervical cancer can expect minimal benefit at the cost of significant toxicity. Quality of life considerations should be of paramount importance when counseling regarding the risks and benefits of further cytotoxic therapy.